2018
DOI: 10.1007/s00726-018-2594-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety of dietary supplementation with arginine in adult humans

Abstract: Previous studies with animals and humans have shown beneficial effects of dietary supplementation with L-arginine (Arg) on reducing white fat and improving health. At present, a long-term safe level of Arg administration to adult humans is unknown. The objective of this study was to conduct a randomized, placebo-controlled, clinical trial to evaluate the safety and tolerability of oral Arg in overweight or obese but otherwise healthy adults with a body mass index of ≥ 25 kg/m. A total of 142 subjects completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 80 publications
0
40
0
1
Order By: Relevance
“…For example, Alvares, Conte‐Junior, Silva, and Paschoalin (2014) reported that l ‐arginine supplementation to humans for four weeks did not promote any beneficial changes in metabolic and hormonal parameters (Alvares et al, 2014), whereas Forbes and Bell (2011) observed no significant difference in GH and glucose following acute consumption of l ‐arginine (Forbes & Bell, 2011). Similarly, chronic oral administration of 15 or 30 g arginine/day to obese and overweight adults had no discernible effect on the plasma concentrations of GH or insulin (McNeal et al, 2018). It thus seems likely that the response of humans to arginine is dependent on their metabolic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Alvares, Conte‐Junior, Silva, and Paschoalin (2014) reported that l ‐arginine supplementation to humans for four weeks did not promote any beneficial changes in metabolic and hormonal parameters (Alvares et al, 2014), whereas Forbes and Bell (2011) observed no significant difference in GH and glucose following acute consumption of l ‐arginine (Forbes & Bell, 2011). Similarly, chronic oral administration of 15 or 30 g arginine/day to obese and overweight adults had no discernible effect on the plasma concentrations of GH or insulin (McNeal et al, 2018). It thus seems likely that the response of humans to arginine is dependent on their metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine may also affect multiple metabolic pathways involving amino acid degradation (Blachier, Davila, Benamouzig, & Tome, 2011), nutrient transport (Kim & Wu, 2009) and cellular redox state (Wu, 2009; Yin & Tan, 2010). Recent studies have shown that dietary supplementation with arginine can reduce plasma levels of glucose, fatty acids, homocysteine and asymmetric dimethylarginine (McNeal, Meininger, Wilborn, Tekwe, & Wu, 2018), while improving endothelium‐dependent relaxation in both type I and type II models of diabetes mellitus (Fu et al, 2005). Dietary arginine supplementation also alters amino acid concentrations in the plasma of swine, enhances protein synthesis in skeletal muscle and modulates intestinal microbial metabolites (He et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That observation was similar to findings from a single female patient with an inherited metabolic disorder [31] and from patients with non-alcoholic fatty liver disease [32], who were also characterized by a serine supplementation-induced drop in circulating branched-chain amino acids, which was not seen in the present trial. In parallel to previous phenylalanine and serine studies [30][31][32] and to clinical safety studies with other amino acids [15,33], plasma changes in tyrosine and serine were not considered pathological because they were transient, unaccompanied by imbalances of other amino acids and unconnected to any changes in the evaluated behavioral parameters. An increase in plasma tyrosine measured when phenylalanine was supplemented at 12 g/day might have hypothetically affected the brain catecholamines and thus reduced stress and mental fatigue [34].…”
Section: Sleep Quality Mental Fatigue Macronutrient and Caloric Intakes Body Weight Changesmentioning
confidence: 99%
“…RATIONALE: The risk assessment of regulated substances without history of use (e.g., high-intensity sweeteners) relies on in vitro and animal studies through established "classical toxicology" methodologies. Such approaches are not applicable to macronutrients with evolutionary food history, as illustrated in significant divergences in NOAELs derived from rodent and human sub-chronic evaluations of the amino acid methionine [14,15], leucine [16,17], and arginine [18,19].…”
Section: Comment 2a: Icaas Supports the Emphasis On Human Data In Developing Hbgvs For Nutrients Such Asmentioning
confidence: 99%